2020
DOI: 10.1029/2019jb018575
|View full text |Cite
|
Sign up to set email alerts
|

SKS Splitting Measurements in NE China: New Insights Into the Wudalianchi Intraplate Volcanism and Mantle Dynamics

Abstract: To better understand the Wudalianchi intraplate volcanism and mantle dynamics in NE China, we collect abundant teleseismic waveform data during 2008 to 2018 recorded at 259 seismic stations around the Wudalianchi volcano. These stations include 148 WAVESArray portable stations, 66 NECESSArray portable stations and 45 Chinese provincial stations. Our newly deployed WAVESArray makes the station intervals of ~20–30 km around the Wudalianchi volcano. Using the minimum transverse‐energy grid‐search method, we make … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 74 publications
3
18
0
Order By: Relevance
“…Furthermore, the E‐W FPD is dominated around the Changbaishan and Longgang volcanoes, whereas an NW‐SE FPD is found around the Wudalianchi volcano (Figures 9 and 10). The upper mantle anisotropy could be related to the preferred orientation of olivine lattice caused by tectonic deformation, thus all these results could imply that there may exist material and energy exchanges among the volcanoes, which might be due to complicated horizontal mantle flows rather than simple southeastward mantle flow in the BMW, probably because of the hard obstacles with high‐V anomalies (Figures 10 and 18; e.g., Chen et al., 2017; Lei & Zhao, 2005, 2006; Lei et al., 2013, 2018; M. Lu et al., 2020; Zhao, 2004; Wei et al., 2015; B. Zhang et al., 2020).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, the E‐W FPD is dominated around the Changbaishan and Longgang volcanoes, whereas an NW‐SE FPD is found around the Wudalianchi volcano (Figures 9 and 10). The upper mantle anisotropy could be related to the preferred orientation of olivine lattice caused by tectonic deformation, thus all these results could imply that there may exist material and energy exchanges among the volcanoes, which might be due to complicated horizontal mantle flows rather than simple southeastward mantle flow in the BMW, probably because of the hard obstacles with high‐V anomalies (Figures 10 and 18; e.g., Chen et al., 2017; Lei & Zhao, 2005, 2006; Lei et al., 2013, 2018; M. Lu et al., 2020; Zhao, 2004; Wei et al., 2015; B. Zhang et al., 2020).…”
Section: Discussionmentioning
confidence: 94%
“…Ambient noise tomography by Yang et al (2019) revealed low-V anomalies in the upper and middle crust and upper mantle but high-V anomalies in the lower crust under the Wudalianchi volcano, suggesting an intermittent mantle magma provision. SKS splitting measurements by M. Lu et al (2020) show a southeastward opening U-shaped structure in the fast direction and splitting time around the Wudalianchi volcano, suggesting the coexistence of both vertical mantle flow under the volcano and horizontal mantle flow around the volcano obstructed by the thicker lithosphere under the Great Xing'an range.…”
Section: Northeast Chinamentioning
confidence: 94%
“…The existence of the rigid slab segment or thick lithospheric keel could deflect the APM‐induced NW‐SE mantle flow to travel along the edges, leading to the observed NE‐SW fast orientations (Figure 7). Such a deflected flow system has been widely employed to explain SWS measurements along the edges of regions with thick lithospheric roots such as the North American continent (Fouch et al., 2000; Refayee et al., 2014; Yang et al., 2017), the Great Xing'an range in NE China (Lu et al., 2020), cratons in southern Africa (Reed et al., 2017; Y. Yu et al., 2015) and continental keels beneath the South Carpathians (Song et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Seismic waveforms used in this study are collected from one permanent network and seven portable arrays, consisting of 145 permanent CEA stations (Zheng et al, 2010), 127 portable NECESSArray stations (Tao et al, 2014), 60 portable NECsaids stations (Wang et al, 2016), 40 portable NECsaids3 stations (Zhang et al, 2020), 42 portable WDLC stations (Lu et al, 2020), 20 portable DXAL stations (Peng et al, 2019), 6 portable XM stations (Zhang and Wu, 2019), and 6 portable NK stations (Ri et al, 2016). Detailed information about the number of stations and operating time range for each network is summarized below in Table S1.…”
Section: Seismic Datamentioning
confidence: 99%